PENGARUH KUALITAS PELAYANAN, FASILITAS, DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA RESTORAN VELVET HOTEL GUNAWANGSA MERR - Yohana Eflina Jelanu; Stephanie Astrid Ayu (Jurnal AKTUAL, 2023)
This study aims to determine the effect of service quality, facilities, and prices on customer satisfaction at the Velvet Hotel Gunawangsa Merr Restaurant. In this study, the population was the customers of the Hotel Velvet Hotel Gunawangsa Merr. The technique used in sampling in this study was non-probability sampling with a purposive sampling approach with a total sample of 90 respondents. Based on data processing using SPSS version 26, the validity test results in this study resulted in r count ≥ r table (0.2072) with a significant level of 0.05 and all statement items in this study were declared valid. The results of the Reliability Test showed that all variables in this study were reliable by showing Cronbach Alpha values ≥ 0.60. The normality test shows that the regression model in this study meets the assumptions of normality and the data shows a normal distribution pattern. The multicollinearity test in this study resulted in a tolerance value > 0.10 and a VIF value < 10 where multicollinearity did not occur. Heteroscedasticity test showed that in this study there was no heteroscedasticity. Multiple Linear Regression Test, namely, Y = 6.447 + 0.75 (X1) + 0.809 (X2) + 0.297 (X3). The Coefficient of Determination test (R2) yields an Adjusted R Square value of (0.809) which indicates the independent variable has a strong contribution to the dependent variable. The results of the t test obtained Service Quality (X1) did not affect Service Quality at the Velvet Hotel Gunawangsa Merr Restaurant (Y) with a t count of 0.533 < t table (1.66277) significant 0.595 > 0.05. Facilities (X2) have no effect on customer satisfaction at the Velvet Hotel Gunawangsa Merr Restaurant (Y) with a t count of 1.790 > t table (1.66277) with a significant level of 0.432 > 0.05. Price (X3) has a significant effect on service quality at the Velvet Hotel Gunawangsa Merr Restaurant (Y) with a t count of 2.358 > t table (1.66277) a significant 0.021 <0.05. The conclusion of this study is that the quality of service and facilities has no effect on customer satisfaction at the Velvet Hotel Gunawangsa Merr Restaurant and the price has a significant effect on customer satisfaction at the Velvet Hotel Gunawangsa Merr Restaurant.